Antecedent avian immunity limits tangential transmission of West Nile virus to humans. - Jennifer L Kwan (Public Library of Science (PLoS), 2012)
Background West Nile virus (WNV) is a mosquito-borne flavivirus maintained and amplified among birds and tangentially transmitted to humans and horses which may develop terminal neuroinvasive disease. Outbreaks typically have a three-year pattern of silent introduction, rapid amplification and subsidence, followed by intermittent recrudescence. Our hypothesis that amplification to outbreak levels is contingent upon antecedent seroprevalence within maintenance host populations was tested by tracking WNV transmission in Los Angeles, California from 2003 through 2011. Methods Prevalence of antibodies against WNV was monitored weekly in House Finches and House Sparrows. Tangential or spillover transmission was measured by seroconversions in sentinel chickens and by the number of West Nile neuroinvasive disease (WNND) cases reported to the Los Angeles County Department of Public Health. Results Elevated seroprevalence in these avian populations was associated with the subsidence of outbreaks and in the antecedent dampening of amplification during succeeding years. Dilution of seroprevalence by recruitment resulted in the progressive loss of herd immunity following the 2004 outbreak, leading to recrudescence during 2008 and 2011. WNV appeared to be a significant cause of death in these avian species, because the survivorship of antibody positive birds significantly exceeded that of antibody negative birds. Cross-correlation analysis showed that seroprevalence was negatively correlated prior to the onset of human cases and then positively correlated, peaking at 4-6 weeks after the onset of tangential transmission. Antecedent seroprevalence during winter (Jan - Mar) was negatively correlated with the number of WNND cases during the succeeding summer (Jul-Sep). Conclusions Herd immunity levels within after hatching year avian maintenance host populations <10% during the antecedent late winter and spring period were followed on three occasions by outbreaks of WNND cases during the succeeding summer. Because mosquitoes feed almost exclusively on these avian species, amplification was directly related to the availability of receptive non-immune hosts.